Determination of inorganic arsenic in Argentinean rice by selective HGAAS: Analytical performance for paddy, brown and polished rice - Schlotthauer, Jonatan; Brusa, Lucila; Liberman, Claudia Alejandra; Durand, Mariano; Livore, Alberto Blas; Sigrist, Mirna (Elsevier, 2020)
Inorganic As (iAs) species require strict monitoring in foodstuff due to their toxicity. Rice is of particular concern, with recent legislations establishing limits for these species. In this work we develop a method based on selective hydride generation atomic absorption spectrometry (HGAAS) for the determination of iAs in different types of rice (polish, parboiled, brown and paddy rice). The multivariate design of experiments used for optimization showed interactions between different factors involved in hydride generation. Matrix effects were systematically studied, where the flow rate of the carrier gas proved to be a critical parameter for the minimization of matrix interferences. Nevertheless, matrix-matching was found to be necessary for accurate quantification of paddy rice samples. Comparison of the iAs concentrations obtained by HGAAS and HPLC-ICP-MS showed non-significant differences between the methods. Analysis of 86 rice samples from the province of Entre Ríos showed relatively low concentrations of iAs (<282 μg kg−1 for paddy rice and <120 μg kg−1 for polished rice), regardless of total As concentrations (which ranged from 63 μg kg−1 to 932 μg kg−1), suggesting that the rice analyzed tends to accumulate As in its organic forms.